Stay local or go regional? Urban form effects on vehicle use at different spatial scales: A theoretical concept and its application to the San Francisco Bay Area - Milakis, Dimitris; Cervero, Robert; van Wee, Bert (Journal of Transport and Land Use, 2015)
This paper explores the respective roles of local and regional characteristics of urban form on vehicle travel. We hypothesize that the effects of urban form on vehicle use at the local and regional levels are complementary, and we introduce the concept of local and regional action spaces, which are defined based on the accessibility of alternative means of transport within an acceptable travel time, to test this hypothesis. Multilevel and ordered logit models are developed for the San Francisco Bay Area to estimate the effects of urban form and socioeconomic characteristics on vehicle kilometers traveled (VKT) and vehicle trip frequency (for work, shopping, and social/recreational purposes). We find that the two urban scale characteristics exert complementary effects on VKT. However, because people in the San Francisco Bay Area display significantly lower VKT in the local than in the regional action space, we conclude that regional-scale inter-ventions would contribute more to the policy objective of VKT reduction, alt-hough local-scale design policies might also help reach this policy goal. Intersec-tion density (for the local action space models) and regional jobs accessibility (for the regional action space models) demonstrated the strongest and most significant relationships with VKT. The built environment did not appear to significantly affect vehicle trip frequency, which is likely due to the uniformly high levels of vehicle use in both the local and regional action spaces in the area.